2006
DOI: 10.1300/j222v04n03_02
|View full text |Cite
|
Sign up to set email alerts
|

Capriciousness or Fairness?

Abstract: Previous research on capital sentencing have discovered quantitative proof of discrimination, especially by race of the victim. The present study examines prosecutorial decision making in Kentucky. Using a method of analysis developed by Berk et al., it seeks to determine the level of capriciousness (uncertainty) present in the prosecutorial decision to seek the death penalty. Kentucky prosecutors were most likely to seek the death penalty in cases where black offenders killed white victims.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Contrary to prior research suggests that capital trial outcomes may be affected by the race characteristics of both the defendant and victim (Keil and Vito, 1995;Thomson, 1997;Williams et al, 2007), our findings are consistent with the findings reported by . Our results did not provide empirical support for the notion that either defendant or victim demographic characteristics were directly associated with the outcomes of the U.S. Attorney General's review.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Contrary to prior research suggests that capital trial outcomes may be affected by the race characteristics of both the defendant and victim (Keil and Vito, 1995;Thomson, 1997;Williams et al, 2007), our findings are consistent with the findings reported by . Our results did not provide empirical support for the notion that either defendant or victim demographic characteristics were directly associated with the outcomes of the U.S. Attorney General's review.…”
Section: Discussionsupporting
confidence: 86%
“…Findings from the limited amount of prior research have been inconclusive regarding the specific effects of psychological factors in mitigation Beck and Shumsky, 1997;Cowan et al, 1984;Garvey, 1998;Gillespie et al, 2014;Keil and Vito, 1995;McPherson, 1995;Paternoster, 1984;White, 1987). Notably, there have been no published studies that specifically examine mental health data as mitigating evidence on federal case outcomes, nor has investigation queried the impact of such evidence on the U.S. Attorney General's authorization to seek the death penalty.…”
Section: Mental Illness Mitigationmentioning
confidence: 99%
See 1 more Smart Citation
“…Research that has examined conviction outcomes highlights cases resulting in wrongful convictions (Free & Ruesink, 2012;M. B. Johnson, 2020;Ruesink & Free, 2005), the death penalty (Harmon, 2004;Holcomb et al, 2004;Keil & Vito, 2006;Ulmer et al, 2020;williams et al, 2007), and specific types of violent offenses (e.g., rape, domestic violence, and child sexual assault; Golding et al, 2007;La Free, 1980;Lundrigan et al, 2020;Nelson, 2013). For example, wagner and colleagues (2016) explore the factors that influence the odds of conviction in Stand your Ground (SyG) cases adjudicated in Florida and found that cases with non-white victims and those in which a gun was used in the attack were less likely to result in conviction.…”
Section: Convictionmentioning
confidence: 99%